THE RELATIONSHIP BETWEEN DEMOGRAPHIC FACTORS AND INVESTMENT DECISION IN SURABAYA - Lutfi Lutfi (Journal of Economics, Business, and Accountancy Ventura, 2010)
The financial literature supports an increasing role for behavioral aspects of investment decision making. Among other factors, demographic factor may influence investors’ risk tolerance and investment preferences. This paper explores the relationship between demo- graphic factors, such as gender, age, marital status, education, income, and family members, and investor’s risk tolerance as well as investment preference. First of all, it attempts to reveal the relationship between investor’s demographic factors (gender, age, marital status, education, income, and number of family) and investor’s risk behavior (risk seeker, risk averse. Secondly, it tries to see the relationship between investor’s demographic factors (gender, age, marital status, education, income, and number of family) and types of invest- ment (bank products, capital market instruments, and physical assets). Finally, it endeavors to uncover the relationship between investor’s demographic factors (gender, age, marital status, education, income, and number of family) and types of investment (bank products, capital market instruments, and physical assets). Using a sample of 84 investors in Surabaya, this study shows that demographic factors explain investor’s risk tolerance and investment preference. The results also reveal a significant relationship between investors’ risk toler- ance and their investment preferences.